Leishmaniasis in Turkey: Determination of Leishmania Species by Matrix-Assisted Laser Desorption Ionization Time-Of-Flight Mass Spectrometry (MALDI-TOF MS) - CULHA, Gülnaz (Iran J Parasitol, 2014)
BACKGROUND: Cutaneous leishmaniasis (CL) is endemic in Southeastern Anatolia, mainly in Sanliurfa and Hatay provinces, and the causative agents are mostly Leishmania tropica and less frequently L. infantum. Here, we report the first MALDI-TOF analyses of Leishmania promastigotes obtained from the cultures of two CL cases from Osmaniye and Hatay provinces who were initially diagnosed by microscopy, culture and identified as L. infantum with Real-Time PCR (RT-PCR). METHODS: Samples obtained from the skin lesions of patients were initially stained with Giemsa and cultivated in NNN medium. Examination of the smears and cultures revealed Leishmania amastigotes and promastigotes, respectively. The promastigotes (MHOM/TR/2012/CBU15 and MHOM/TR/2012/MK05) obtained from the cultures of both patients were used for RT-PCR targeting the ITS-1 region in the SSU of rRNA. The reference strains of four Leishmania species (L. infantum, L. donovani, L. tropica and L. major) were initially assessed with MALDI-TOF and their data were added to MALDI-TOF Biotyper Library. RESULTS: Both RT-PCR and MALDI-TOF analyses indicated that the causative agent in both patient samples was L. infantum. CONCLUSION: Despite disadvantages such as requirement of culture fluid with nothing but promastigotes and high cost, MALDI-TOF analysis may be a fast, sensitive and specific diagnostic tool in especially large-scale research studies, where the cost declines, relatively.